Sensory Experience, Perceived Price, and Customer Satisfaction: Drivers of WOM Recommendation - Tommy Setiawan Ruslim; Claudia Gita Hapsari (Jurnal Mirai Management, 2025)
This study investigates the influence of sensory experience and perceived price on word-of-mouth (WOM) recommendation, with customer satisfaction as a mediating variable, in the context of Wolf Gang’s Steakhouse Jakarta. Using the Stimulus-Organism-Response (SOR) framework, sensory experience and perceived price serve as stimuli, customer satisfaction as the organism, and WOM recommendation as the response. Data were collected through purposive sampling from 218 respondents who had dined at the restaurant. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. Results reveal that sensory experience and perceived price have significant positive effects on customer satisfaction, which in turn significantly influences WOM recommendation. Additionally, both sensory experience and perceived price directly and indirectly affect WOM recommendation through partial mediation by customer satisfaction. These findings highlight the importance of enhancing sensory aspects such as taste, aroma, presentation, and freshness, alongside maintaining fair and transparent pricing, to improve satisfaction and encourage positive WOM. The study contributes theoretically by reinforcing the mediating role of customer satisfaction in the SOR model and provides practical insights for fine dining managers to improve customer experiences and strengthen competitive positioning. Keywords: Sensory Experience, Perceived Price, Customer Satisfaction, WOM Recommendation